COOPERATIVE LEARNING ON EFL PROFICIENCY; THE BEST PRACTICE AT ISLAMIC HIGH SCHOOL STUDENTS - Andriyono, Andriyono (IKIP Mataram, 2020)
The study was aimed at finding out the effectiveness of the cooperative language learning on students' English proficiency as measured by their abilities in grammar, reading comprehension, vocabulary and listening comprehension. The study also sought to measure students? attitude towards cooperative learning and motivation to learn English. This study was a comparative research design in the form of non-equivalent control group design. The experiment lasted for twelve weeks in which two intact groups from two Class of MAN 2 Praya were chosen as the study groups. Subjects of this study consist of 44 students who attended classes. The control group includes 53 students. This study tested the effectiveness to examine the method; two quantitative tools for data collection were used to compile the findings of the study. For starters, a pre- and a post-test were administered to measure English proficiency before and after the treatment. Afterward, a questionnaire was set to measure students? attitude towards cooperative learning and motivation to study English in new high school system. After analyzing the data, the results indicated that cooperative learning in the new system positively affect some aspects in the participants? English proficiency and they had a positive attitude towards cooperative learning in the new system and a higher motivation to learn English.